Analisis Efektivitas Platform SIAPKerja Dalam Transformasi Pelayanan Pembuatan Kartu Kuning (AK 1) dan Informasi Lowongan Kerja di Dinas Tenaga Kerja Kota Cilegon - Hilyah Maulidah; Gatot Hartoko; Ita Rosita Wahyiah (Universitas Serambi Mekkah, 2026)
Unemployment poses a significant challenge to the labor sector in Indonesia, including in Cilegon City. To enhance employment services, the Cilegon City Manpower Office has implemented the SIAPKerja Platform as a digital innovation for